1991
DOI: 10.1021/bi00215a030
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic spectrum resulting from DNA damage by oxygen radicals

Abstract: Oxygen free radicals are highly reactive species that damage DNA and cause mutations. We determined the mutagenic spectrum of oxygen free radicals produced by the aerobic incubation of single-stranded M13mp2 DNA with Fe2+. The Fe2(+)-treated DNA was transfected into component Escherichia coli, and mutants within the nonessential lac Z alpha gene for beta-galactosidase were identified by decreased alpha-complementation. The frequency of mutants obtained with 10 microM Fe2+ was 20- to 80-fold greater than that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
95
1

Year Published

1992
1992
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(99 citation statements)
references
References 45 publications
3
95
1
Order By: Relevance
“…Anthracycline drugs, such as epirubicin, exhibit strong redox cycling properties within the cell and can generate a signi®cant amount of DNA-damaging hydroxyl radicals (Kappus, 1986;Cervantes et al, 1988;Keizer et al, 1990;Turner III et al, 1990;Doroshow, 1996). The mutations observed at GC base pairs within the p53 genes of both patients 2 and 3 would be consistent with a mechanism involving radical ion attack of guanine or cytosine DNA base residues (Muindi et al, 1985;McBride et al, 1991;Akman et al, 1992). Long term exposure to epirubicin could select for canine lymphoma cells containing therapy-induced p53 gene mutations and displaying a chemoresistant phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…Anthracycline drugs, such as epirubicin, exhibit strong redox cycling properties within the cell and can generate a signi®cant amount of DNA-damaging hydroxyl radicals (Kappus, 1986;Cervantes et al, 1988;Keizer et al, 1990;Turner III et al, 1990;Doroshow, 1996). The mutations observed at GC base pairs within the p53 genes of both patients 2 and 3 would be consistent with a mechanism involving radical ion attack of guanine or cytosine DNA base residues (Muindi et al, 1985;McBride et al, 1991;Akman et al, 1992). Long term exposure to epirubicin could select for canine lymphoma cells containing therapy-induced p53 gene mutations and displaying a chemoresistant phenotype.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, the mammalian bypass DNA polymerase Pol preferentially incorporates T and to a lesser extent G opposite 5-OHU (19). The T⅐5-OHU pair would result in GC 3 TA transversion as frequently observed in vivo (22). In contrast, only the correct nucleotide G is inserted opposite 5-OHC (19).…”
Section: Discussionmentioning
confidence: 96%
“…Elevated mucosal ROS concentrations have been demonstrated by chemiluminescence in mucosal biopsy specimens from patients with macroscopic oesophagitis and from patients with BarrettÕs metaplasia with or without oesophagitis (Olayee et al, 1995). Free radicals injure cell membranes and are mutagenic (Hinder and Stein, 1991;McBride et al, 1991). Huot et al (1996) demonstrated that overexpression of Hsp27 provides protection against actin disruption and cell death by oxyradicals.…”
Section: Discussionmentioning
confidence: 99%